My head master - Lilymjok, Kyuka (Malthouse Press Limited, 2017)
"I first time I saw the man who became my headmaster was when he rode his motorcycle past our house in Tyosa. He was a huge, dark, hairy man with big eyeballs that looked like they could see through anything and often saw through everything. His eyes were so frightening to me that I always trembled whenever he turned them on me. Not only were the eyeballs big, he had a way of baring them in the most frightening manner when he focused them on you. Older people said his father Akut was nicknamed Akut the owner of frightening eyes for pretty much the same reason. His eyeballs were said to be so big as to scare away birds whenever he entered the forest. Some people said they scared away chickens too. So he was called Akut the owner of frightening eyes ... "But Akut's son was headmaster and no one dared pass his nickname to his son though he had passed his frightening eyes to the son. No one dared sing songs behind him the way children used to sing behind Akut his father ..." Passing through and growing up in school with Akut's son as the Headmaster, and what it took to grow up in a closely-knit community through the eyes and memory of a pupil is a story that has to be told, the story of any pupil. And this is the story ...